The Creep of Frozen Sands: Qualitative and Quantitative Models. - Ting,John M (1981)
This Report developes better qualitative and quantitative models for the time-dependent mechanical behavior of frozen soils. By drawing upon an extensive literature survey, unconfined creep data for frozen sand, and a series of creep tests on glass beads made wetting and nonwetting, various physical mechanisms controlling the behavior of frozen soil and proposed: ice strength, soil strength, and mechanical interaction through structural hindrance and dilatancy effects. The nature of the linear relationship between the logarithm of the minimum creep rate and the logarithm of the time to minimum observed from creep tests on ice, soil and frozen soil is shown to be due to the existence of an approximately constant strain at the minimum, and the relative insensitivity of this log-log plot to small deviations from a constant value of strain. Two quantitative models for fitting and predicting the minimum strain rate and time to minimum for unconfined creep are developed and evaluated. Each can typically predict the minimum strain rate and time to minimum to within + or - 4 times the actual value using data from only a relatively few tests. New empirical creep models capable of describing the entire creep curve from primary through tertiary are also developed. Through a simple technique for parameter evaluation, the models can yield excellent fits of the data and reliable predictions of the creep behavior. Typically, the model predict the minimum strain rate to within + or - 3 times and the strain at the minimum to within 70% of the actual values. (Author) See also AD-A075 297.